MINI-REVIEW PEMBELAJARAN DARING SELAMA PANDEMI COVID-19: KEUNTUNGAN DAN TANTANGAN - Elina Lestariyanti (Jurnal Prakarsa Paedagogia, 2020)
The emergence of COVID-19 has an impact on the world of education. The learning process that is commonly carried out face-to-face in class must change to distance learning using online learning. This article aims to review research articles on the advantages and challenges of online learning during the COVID-19 pandemic. The research method uses the literature review method of research articles on the application of online learning during the COVID-19 pandemic published in 2020. The results of the review show the advantages of using online learning can be classified into two categories, namely the advantages in the area of processes and area of impacts. The challenges of using online learning are internet access, the burden of quota costs, the availability and support of technology or devices. Teacher creativity, student characteristics, environmental support and geographical conditions are also challenges that need to be considered so that the achievement of learning outcomes through online learning can be optimized.